Assessing the impact of roads on the ecological state of the environment (Eurasian Journal of Ecology, 2016)
The article considered the state of the roads, the impact of construction works on the environment, are the way they are identified. We discuss the main requirements to the highways, as well as reducing the harmfuleffects of roads on the ecological environment.
Keywords: road; environment; car; ecology; requirements; economics pavement